Uji efektivitas ekstrak etanol kulit buah naga merah (Hylocereus polyrhizus) terhadap Staphylococcus aureus ATCC 25923 secara in vitro - Anak Agung Bintang Astridwiyanti; Agung Nova Mahendra; Ni Wayan Sucindra Dewi (Intisari Sains Medis, 2019)
Introduction: Infectious diseases are still one of the main causes of high morbidity and mortality in tropical Indonesia. One of the causes of this disease is the staphylococcus aureus bacteria. Red dragon fruit peel contains potentially antibacterial compounds such as flavonoid, alkaloid, saponin, tannin dan terpenoid. The purpose of this study is to determine the antibacterial activity of ethanolic extract of red dragon fruit peel against staphylococcus aureus ATCC 25923.Method: The method used is true experimental post test only control group design. The activity of ethanol extract of red dragon fruit skin was tested in various concentrations (25%, 50%, 75%, and 100%) against staphylococcus aureus ATCC 25923 by measuring the inhibition zone diameter and minimum inhibitory concentration (MIC).Result: The results of this study show that red dragon fruit peel ethanolic extract has antibacterial activity against staphylococcus aureus ATCC 25923 ith the average diameter of inhibition zone ranging from 8.25 mm – 12.5 mm. The MIC is obtained at concentration of 25%. Kruskal-Wallis test found a significant comparison with a value of p = 0,000 (p value <0.05). Mann-Whitney test showed that there were significant differences between each concentration, except the concentration of 50% did not have a significant difference with a concentration of 75%.Conclusion: The minimum inhibitory concentration (MIC) is produced by extract at a concentration of 25% and the best inhibitory zone produced by 100% concentration of red dragon peel ethanol extract.